1987
DOI: 10.1002/eji.1830170320
|View full text |Cite
|
Sign up to set email alerts
|

Ir gene control of the murine secretory IgA response to cholera toxin

Abstract: In these experiments we examined the genetic control of the secretory IgA (sIgA) response to cholera toxin (CT) after CT feeding. Inbred, congenic and intra-H-2I region recombinant mouse strains were immunized with intragastric application of 10 micrograms CT on days 0 and 14. Samples of intestinal secretions and plasma were collected 1 week after the second dose and antibodies to CT measured in them by antigen- and isotype-specific enzyme-linked immunosorbent assay. In three different sets of H-2-congenic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Therefore, these results suggest that the serum antibody response to the cell fraction of the orally administered lactic acid bacteria was closely related to the proliferative response ofPP to the cell fraction. This is consistent with the results of Elson and Ealding, 22) who have found that the serum antibody response produced by cholera toxin feeding was due to the immune response of PP to the cholera toxin, rather than of other lymphoid tissues such as the spleen.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these results suggest that the serum antibody response to the cell fraction of the orally administered lactic acid bacteria was closely related to the proliferative response ofPP to the cell fraction. This is consistent with the results of Elson and Ealding, 22) who have found that the serum antibody response produced by cholera toxin feeding was due to the immune response of PP to the cholera toxin, rather than of other lymphoid tissues such as the spleen.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, recent evidence suggests that an innate component of the immune system may also play a role in the host response to cholera (9,22,26). Studies with experimental animals have shown that the mucosal immune response to cholera toxin is T cell dependent and that CD4 T helper cells have an important role (7,12,13). However, not much is known about the role of the adaptive cellular immune responses in patients with cholera.…”
mentioning
confidence: 99%
“…Various studies in mice have shown that oral tolerance is influenced by strain, 20,21 age at first feeding, [22][23][24] and the dose and nature of antigen. 25,26 Cholera toxin, a potent mucosal adjuvant for secretory IgA production in some mouse strains, 27,28 has been shown to activate T H2 cells and promote production of IL-4 and IgE antibodies. 29,30 We recently used a combination of experimental conditions to generate the first murine model of IgE-mediated cow's milk hypersensitivity (CMH), which closely resembles the clinical features of immediate cow's milk allergy in human subjects.…”
mentioning
confidence: 99%